Evaluating the Effects of Clinical Characteristics and Therapeutic Regimens on Mortality in Hospitalized Patients with Severe COVID-19 - Elahe Karimpour-Razkenari; Javad Boskabadi; Monireh Ghazaeian; Hamidreza Samaee; Hanieh Azizi; Fatemeh Esfandiari; Seyed Abdollah Mousavi; Sahar Fallah; Sekineh Talebi (Research Center for Rational Use of Drugs (RCRUD), 2022)
Background: The coronavirus disease 2019 (COVID-19) is highly contagious and has turned into a global health problem.  In this study, we investigated the role of clinical and laboratory characteristics along with administered therapeutic agents in patients with COVID-19, and identified some effective factors on the mortality of these individuals. Methods: In this retrospective study, we evaluated the data from all the hospitalized patients who had been diagnosed with COVID-19 between February 23 and May 23, 2020. The data were obtained from medical records. Additionally, a checklist was used to record demographic, clinical, laboratory, imaging, and treatment data for each patient. Results: Totally, 478 patients were involved in this study, and their median age was 58.5 years. Of these, 53.3% patients were male. The most common pre-existing underlying disease was hypertension (37.9%), and the mortality group had significantly more comorbidities (85.4%).  Higher neutrophil lymphocyte ratio (NLR), lymphopenia, and reduced hemoglobin were more frequent in the mortality group (p < 0.001).  Similarly, the need to be admitted to the intensive care unit was significantly greater in the mortality group (p<0.001). The most frequently administered therapeutic regimens included hydroxychloroquine and lopinavir/ritonavir, which did not have any correlation with survival outcome. Conclusion: Older age, opioid addiction, cardiovascular disease, kidney disease, baseline NLR and hemoglobin, and ICU admission were independently associated with COVID-19 mortality. On the other hand, hydroxychloroquine and lopinavir/ritonavir indicated no beneficial effects on patients' outcome.